A necroptosis‐related gene signature for predicting prognosis, immune landscape, and drug sensitivity in hepatocellular carcinoma. (13th May 2022) - Chen, Junliang; Wang, Huaitao; Zhou, Lei; Liu, Zhihao; Chen, Hui; Tan, Xiaodong
Abstract: Background: Hepatocellular carcinoma (HCC) remains a growing threat to global health. Necroptosis is a newly discovered form of cell necrosis that plays a vital role in cancer development. Thus, we conducted this study to identify a predictive signature of HCC based on necroptosis‐related genes. Methods: The tumor samples in the liver hepatocellular carcinoma (LIHC) cohort from The Cancer Genome Atlas (TCGA) database were subtyped using the consensus clustering algorithm. Univariate Cox regression and LASSO‐Cox analysis were performed to identify a gene signature from genes differentially expressed between tumor clusters. Then, we integrated the TNM stage and the prognostic model to build a nomogram. The gene signature and the nomogram were externally validated in the GSE14520 cohort from the Gene Expression Omnibus (GEO) and the LIRP‐JP cohort from the International Cancer Genome Consortium (ICGC). Evaluations of predictive performance evaluations were conducted using Kaplan–Meier plots, time‐dependent receiver operating characteristic curves, principal component analyses, concordance indices, and decision curve analyses. The tumor microenvironment was estimated using eight published methods. Finally, we forecasted the sensitivity of HCC patients to immunotherapy and chemotherapy based on this gene signature. Results: We identified two necroptosis‐related clusters and a 10‐gene signature (MTMR2, CDCA8, S100A9, ANXA10, G6PD, SLC1A5, SLC2A1, SPP1, PLOD2, and MMP1). The gene signature and the nomogram had good predictive ability in the TCGA, ICGC, and GEO cohorts. The risk score was positively associated with the levels of necroptosis and immune cell infiltrations (especially of immunosuppressive cells). The high‐risk group could benefit more from immunotherapy and some chemotherapeutics than the low‐risk group. Conclusion: The necroptosis‐related gene signature provides a new method for the risk stratification and treatment optimization of HCC. The nomogram can further improve predictive accuracy. Abstract : Necroptosis is a newly discovered form of cell necrosis that plays a vital role in cancer development. We identified a necroptosis‐related gene signature based on the TCGA cohort, which was validated externally in the ICGC‐LIRI‐JP and GSE14520 cohorts. Our study linked necroptosis with the prognosis, immune landscape, and drug sensitivity of HCC patients.